Locating legal certainty in patent licensing - Bharadwaj, Ashish, 1985-; Devaiah, Vishwas H.; Gupta, Indranath (Springer, 2023)
This open access book presents global perspectives and developments within the information and communication technology (ICT) sector, and discusses the bearing they have on policy initiatives that are relevant to the larger digital technology and communications industry. Drawing on key developments in India, the USA, UK, EU, and China, it explores whether key jurisdictions need to adopt a different legal and policy approach to address the unique concerns that have emerged within the technology-intensive industries. The book also examines the latest law and policy debates surrounding patents and competition in these regions. Initiating a multi-faceted discussion, the book enables readers to gain a comprehensive understanding of complex legal and policy issues that are beginning to emerge around the globe. .
Keywords: Patent licenses.; Patent laws and legislation.; Information technology -- Law and legislation.; Licences de brevets.; Entertainment & media law.; International law.; International economic & trade law.; Comparative law; Conflict of laws; Information technology -- Law and legislation; International law; Law and economics; Mass media -- Law and legislation; FRAND; IPR Policy; Technological Innovation; Competition/Antitrust; Smart Cities; Electronic book.